Diário digital criptografado para auxílio em acompanhamento psicológico - Terceros, Diego Alejandro Bejarano (Brasil, 2023)
When developing, human beings interact with their surroundings and this, in contrast, generates emotions and feelings. Commonly, and to immortalize these experiences, the individual tends to portray these physically on devices such as papers or others. In recent times, the use of the “diary” has been of great importance to people, since it represents what is experienced on a daily basis, and serves therapeutically for the subject in question. Therefore, this course completion work aims to develop a mobile application for the Android platform that will serve as an encrypted digital diary to assist in psychological monitoring. Having thus carried out research that addresses the digital diary as a computational tool for recording emotional data and interpersonal relationships, as well as encryption techniques in mobile systems for the Android platform. Bibliographically, the following descriptors were used: “emotional data records”, “digital diary”, “Android encryption”, “emotional data record”, “e-diary” and “psychological monitoring” in Portuguese and English. Finally, it is concluded that the development of this work created a storage method, which will encrypt the data, structured in the form of a diary that can be accessed by a psychologist, thus making the psychological follow-up of the user more interconnected.